Порушення прав дитини в умовах війни в Україні - Ярмол, Лілія; Карпюк, Анастасія; Yarmol, Liliia; Karpiuk, Anastasiia (Видавництво Львівської політехніки, 2022)
У статті охарактеризовано окремі загальнотеоретичні аспекти прав дитини та основні порушення прав дитини в умовах воєнного вторгнення Російської Федерації на територію України. Мета статті – охарактеризувати основні порушення прав дітей в умовах війни в Україні та сформулювати пропозиції щодо удосконалення механізму забезпечення прав дітей. Під час дослідження використано загальнонаукові (логічний, функціональний, аксіологічний, порівняльний тощо) та спеціально-юридичні методи (метод тлумачення міжнародних і юридичних норм щодо прав дитини, функціонально-правовий, порівняльно-правовий методи – для аналізу порушень прав дитини, статистичний метод та ін.). Стверджується, що максимальне гарантування прав дитини слугує критерієм демократичності держави та визначає рівень розвитку суспільства. Наголошено, що дослідження правових аспектів прав дитини є особливо важливими в умовах повномасштабного воєнного вторгнення Російської Федерації в Україну, яке спричинило значні порушення прав дитини. Визначено поняття прав дитини як можливостей дитини, які визнані в міжнародному праві та національному законодавстві й зумовлені певними фізичними і психологічними особливостями її розвитку, ґрунтуються на принципах природного права, гарантуються державою й іншими суб’єктами права та мають особливий механізм реалізації і захисту. Проаналізовано основні порушення прав дитини в умовах війни в Україні, зокрема права на життя (станом на 19 серпня 2022 р. в Україні загинуло 362 дитини, 716 дітей поранено і 223 дитини зникли безвісти); на охорону здоров’я; на освіту; на свободу вираження поглядів; на свободу, фізичну та психологічну безпеку, на сімейне виховання, житло, на достатній життєвий рівень, на громадянство, вільне переміщення тощо. Стверджується, що в сучасних умовах війни в Україні Російська Федерація порушує фактично усі права дитини. Констатовано, що в Україні потрібно вдосконалювати систему юридичного забезпечення прав дітей, які в умовах війни жорстоко порушуються воєнними діями РФ. Сформульовано пропозиції щодо удосконалення механізму юридичного забезпечення прав дітей в Україні: 1. потрібно прийняти комплексний Закон України про права дитини, який відповідав би положенням Конвенції ООН про права дитини; 2. прийняти суспільно важливі закони щодо дієвої реінтеграції та відновлення прав дитини і про заходи, спрямовані на забезпечення прав та інтересів дітей, які залишились без батьківського піклування під час війни; 3. виділити в Конституції України окремий розділ, присвячений правам дитини. Констатовано, що припинення війни в Україні, притягнення винних осіб до юридичної відповідальності, притягнення РФ як суб’єкта міжнародного права до відповідальності за воєнні злочини, злочини проти людяності, за геноцид українського народу тощо – це важлива основа для відновлення порушених прав дитини й недопущення нових порушень прав.

The article describes certain general theoretical aspects of the rights of a child and the main violations of the rights of the child in the conditions of the military invasion of the Russian Federation on the territory of Ukraine. The purpose of the article is to characterize the main violations of children's rights during the war in Ukraine and to formulate proposals for improving the mechanism for ensuring children's rights. During the research, general scientific (logical, functional, axiological, comparative, etc.) and special legal methods were used (the method of interpretation of international and legal norms regarding the rights of the child, functional-legal, comparative-legal methods - for the analysis of violations of the rights of the child, statistical method, etc.). It is claimed that the maximum guarantee of children's rights serves as a criterion for the democracy of the state and determines the level of development of society. It is emphasized that the study of legal aspects of children's rights is especially important in the conditions of the full-scale military invasion of the Russian Federation into Ukraine, which caused significant violations of children's rights. The concept of child rights is defined as the child's capabilities, which are recognized in international law and national legislation and are conditioned by certain physical and psychological features of its development, are based on the principles of natural law, are guaranteed by the state and other legal subjects, and have a special implementation and protection mechanism. The main violations of children's rights during the war in Ukraine, in particular the right to life (as of August 19, 2022, 362 children were killed in Ukraine, 716 children were injured, and 223 children were missing), to health care, to education, to freedom of expression, to freedom, physical and psychological safety, to family, education, housing, to a sufficient standard of living, to citizenship, free movement, etc. were analyzed. It is claimed that in the current conditions of the war in Ukraine, the Russian Federation violates practically all the rights of the child. It has been established that in Ukraine, it is necessary to improve the system of the legal protection of children's rights, which are brutally violated by the military actions of the Russian Federation during the war. Proposals for improving the mechanism of the legal protection of children's rights in Ukraine were formulated: 1) it is necessary to adopt a comprehensive Law of Ukraine on the rights of the child, which would correspond to the provisions of the UN Convention on the Rights of the Child; 2) adopt socially important laws on effective reintegration and restoration of children's rights and on measures aimed at ensuring the rights and interests of children who were left without parental care during the war; 3) allocate a separate section in the Constitution of Ukraine dedicated to the rights of the child. It was established that ending the war in Ukraine, bringing the guilty parties to justice, bringing the Russian Federation as a subject of international law to responsibility for war crimes, crimes against humanity, the genocide of the Ukrainian people, etc., is an important basis for restoring violated children's rights and preventing new violations of rights.
Violation of the rights of a child in the conditions of war in Ukraine
Keywords: права дитини; війна; порушення прав дитини; юридичне забезпечення; воєнне вторгнення російської федерації; children's rights; war; violation of children's rights; legal support; military invasion of the Russian Federation; 342.7